Functional sol-gel coated electrospun polyamide 6,6/ZnO composite nanofibers - Bedeloğlu, Ayşe; Cin, Zeynep Islek (Walter De Gruyter Gmbh, 2019)
Polymer-based nanofibers are good candidates for medical textiles due to their excellent properties including high surface area, breathability and flexibility. Doping polymer nanofibers with different nanoparticles enhances their existing properties. In this study, electrospun polyamide 6,6 (PA6,6) composite nanofibers containing ZnO nanoparticles (<50 nm) in different amounts (1%, 3% and 5%) were first produced by electrospinning technique; then, these nanofibers were coated with sol-gel ZnO solution (0.5 M) via dip coating method at 1000, 3000 and 5000 mu m/s speeds. The sol-gel coating process increased the breaking strength of nanofiber mats, while the incorporation of ZnO nanoparticles into the polymer nanofibers reduced. Compared to pure PA6,6 nanofiber mats, the ZnO sol-gel coated samples and doped nanofibers had lower reflectance values. In addition, the reflection values decreased as the additive and coating speed increased.
Keywords: composite; electrospinning; nanofiber; polyamide 6,6; sol-gel coating; zinc oxide (ZnO)